Poisson structures on closed manifolds - Mukherjee, Sauvik (Topological Methods in Nonlinear Analysis, 2018)
We prove an h-principle for Poisson structures on closed manifolds. Equivalently, we prove an h-principle for symplectic foliations (singular) on closed manifolds. On open manifolds however the singularities could be avoided and it is a known result by Fernandes and Frejlich Fernandes.